TO DISCLOSE A LESS GENERIC PRONOUN: ADDRESSING NON-BINARY "THEY" - Izzatia Nabila; Slamet Setiawan; Widyastuti Widyastuti (Lakon : Jurnal Kajian Sastra dan Budaya, 2021)
Since the 13th century singular they have been used freely to account to the lack of gender-fair pronoun in the English language.  Singular they that is normally employed as a pronominal non-possessive indefinite singular pronoun, in contrast to an expression on he/she generic. This study aims to provide a linear timeline that accounts to the usage of singular they from 13th century to date. Discerns through the scope of Diachronic studies. This study offers an analysis of context with diachronic relevance. The study uses argumentative cross-examination methods, by combing previous findings conducted by researchers who had undertook and attempted to write under similar theme .The results of this study show periodical changes from 13th century to the next, implying that sociocultural changes may be reflected in linguistic changes. The article postulates some that can be interpreted as lenient acceptance for the application of singular they. This study concludes despite the constant rejection singular they are a proper substitute for the gender-neutral pronoun in the English language due to two major advantages for singular they could afford neutrality and naturalness element in comparison to neologism.